Cu-TiO2 Hybrid Nanoparticles Exhibiting Tunable Photochromic Behavior - Tobaldi, D M
Pure and copper modified photocatalytic TiO2 nanopowders were prepared via a green sol−gel route and heated to 450 °C. Copper does not enter the TiO2 lattice but forms as smaller ∼2 nm Cu based nanocrystals, decorating the surface of ∼10 nm TiO2 nanoparticles. The surface of the larger TiO2 nanoparticles (NPs) is partially covered by much smaller Cu NPs, attached to the surface of the larger NPs but not completely covering them due to the small quantity present (1−10 mol % Cu). This retards the anatase to rutile phase transition and titania domain growth through a grain boundary pinning mechanism. These hybrid nanoparticles show tunable photochromic behavior under both UVA and visible light. Under UVA, Cu2+ nanoparticles reduce to Cu+, and then to Cu0. Under visible light, Cu2+ reduces to Cu+, although to a lesser extent. The induced photochromism can be tuned by varying the light source or exposure time. One mol % Cu causes a reduction of Cu2+, and lowers the d−d absorption band, to 50% after only 12 s, and 95% after 10 min, under UVA light, and has a reduction of 25% in 1 min, 50% in 4 min, and 80% in 1 h under visible light. This is the first report of inorganic compounds, in this case Cu TiO2 hybrid nanoparticles, to exhibit tunable photochromism under both UVA and visible light exposure. This rapid and sensitive effect can potentially be used to modify, tune, or monitor the progress of photoactivated behavior in a new generation of smart/active multifunctional materials and photoactive devices or sensors.